1992
DOI: 10.1001/archinte.1992.00400170138025
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Orthostatic Intolerance

Abstract: In seven patients who presented with lightheadedness, fatigue, "weakness," and sometimes syncope, blood pressure was found not to fall after standing for 3 to 4 minutes but to fall severely, frequently with syncope or presyncopal symptoms, after 13 to 30 minutes when measured every minute with an automatic device. This delayed orthostatic hypotension could be corrected with inflation of a pressure suit to 45 mm Hg. Its mechanism was further investigated with measurements of plasma catecholamines, plasma cortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
1
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(29 citation statements)
references
References 11 publications
2
24
1
2
Order By: Relevance
“…Subsequent chronic therapy confirmed a previous report indicating that octreotide ameliorated chronic fatigue in patients with OI and POTS [13]. We nevertheless encountered prevalent patient dissatisfaction during this study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Subsequent chronic therapy confirmed a previous report indicating that octreotide ameliorated chronic fatigue in patients with OI and POTS [13]. We nevertheless encountered prevalent patient dissatisfaction during this study.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies of drug efficacy in patients with POTS and OI have involved only a brief orthostatic stress and failed to measure standing time as has been previously recommended [13]. The limitations to this study must also be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fitzpatrick et al found that 60° upright tilt reproduced symptoms in 75% of 71 patients with unexplained syncope [21]. We favour our used protocol of the present study because supine resting for at least 30 minutes [22] and long duration of passive upright tilt [23] may increase the sensitivity of the test. Furthermore, by means of our protocol we were able to find orthostatic disorders in 83% of the symptomatic subjects, which suggests a high sensitivity of our method.…”
Section: Discussionmentioning
confidence: 73%
“…If insufficient time is given for the patient to stand before rechecking blood pressure or if an intermediate reading is taken with the patient sitting down, a fall in blood pressure may not be demonstrated. In some patients a significant fall in blood pressure may be noted only after 10 minutes of standing [2].…”
mentioning
confidence: 99%